Bhabinkamtibmas Efforts Through Counseling Activities in Preventing Criminal Acts of Theft with Aggravation in the Kuningan Police Legal Area - Putra, I Made Bayu Dwinata (Police Studies Review, 2024)
Crime of theft with weighting that occurred in Kuningan District is still very high, this is the background to be carried outthis research. Repressive measures are not a solution to overcome the high number of criminal acts of theft by weighting. However, pre-emptive and preventive efforts are the most effective ways to prevent them. Because the perpetrators of theft by weighting emphasize the people who do not have sufficient vigilance or alertness so that the perpetrators can launch the action. Therefore, this study was conducted which aims to find out the implementation of extension activities and determine the factors that hamper the implementation of extension activities by members of Bhabinkamtibmas. This research was conducted using a qualitative approach, using descriptive analysis methods, and data collection techniques in 3 (three) ways, namely interviews, observations, and document studies. Data validation by using data triangulation namely source triangulation and technical triangulation. As for the technique of data analysis using conclusion drawing. Researchers use the theory of routine activities, communication theory, and management theory and use the concept of Bhabinkamtibmas, Guidance Counseling, and the concept of theft with weight to support the research conducted. The results of the findings in a study conducted that Bhabinkamtibmas has carried out counseling activities. However, the implementation was not yet on target and the results obtained were not in line with expectations and the material delivered in the counseling was not comprehensive and was still general in nature. Based on the results of the study, the authors suggest that it can be done by adding personnel, increasing the ability and competence of Bhabinkamtibmas Personnel and increasing facilities for extension activities.